PEMBERIAN KOREKSIAN JAWABAN DISERTAI PENJELASAN UNTUK MEREMEDIASI KESALAHAN PESERTA DIDIK PADA HUKUM NEWTON TENTANG GRAVITASI DI SMA - Hardianti, Renny; Sahala S, Stepanus; Mahmuda, Diah (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractThis research aims to determine the effectiveness of giving feedback in the form of answer sheet correction accompanied by teacher’s explanation to remedy the students’ mistakes in working on the material Newton's law of gravity in SMA Negeri 9 Pontianak. The research method used is Pre-Experimental design with one-group pretest and posttest design. Sampling was done by random sampling with intact group technique which the sample is 33 students of XI MIA 3. The tool of data is in the form of essays consists of 4 questions. The result shows that the largest students’ mistake in the pre-test is on writing formula and calculating which 125 errors. After doing remediation and post-test activities become 36 and 45 errors. However the smallest mistake is writing known and asked which 106 errors. After doing remediation and post-test activities become 30 errors. The number of average decrease in students’ mistake on the material Newton's law of gravity after given remediation by giving feedback in the form of answer sheet correction with teacher's explanation is 69.5%.Providing feedback in the form of answer sheet correction accompanied by teacher’s explanation is effective to remedy the students’ mistake with proportion 0.69 which is moderate. Giving feedback in the form of answer sheet correction accompanied by teacher’s explanations can be used as an alternative way in remediating students’ mistake on the material Newton's law of gravity.   Keywords: Answer sheet Correction, Newton's Law, Mistakes